APPLICATION OF MAGNETO-RHEOLOGICAL DEVICES FOR IMPACT LOADS REJECTION - Mohd Sabirin Rahmat (Tesis, 2020)
This thesis discusses the performance of magneto-rheological (MR) devices in cancelling out the effect of impact energy from the gun system of an armoured vehicle during firing, spefically the performance of magneto-rheological elastomer isolator devices (MREID) and magneto-rheological fluid (MRF) dampers.